The Effect of College Proximity on Rates of College Attendance - Tinto, Vincent ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
The present study attempts to determine the effect of geographic accessibility of a college on the proportion of high school graduates continuing their education beyond school. Specifically, the study asks not only if communities possessing a college send larger proportions of their high school graduates to college than do communities lacking a local college, but also whether these proportions are differentially affected by different kinds of local postsecondary institutions. Since attention is focused on the variant behavior of different types of individuals as defined by sex, ability, and socio-economic background, college accessibility as defined here is not merely an ecological variable but is considered to be a distribution of educational opportunity over socio-economic space. Findings are presented in this document. (Author/HS)
Availability: Columbia University, Teachers College, New York, New York.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Bound Students; College Environment; Colleges; Educational Opportunities; Geographic Location; Higher Education